EVALUASI KUAT GESER BATU PASIR TERHADAP KANDUNGAN AIR - (NIM : 12103033); Pembimbing : Dr. Ir. Suseno Kramadibrata, M.Sc., AMRIZAL
Before desaining mine's slope, we should know rock shear strength's parameters, such as cohesion (c) and internal friction angle value (...). This parameters were found from test at laboratory. Beside those parameters, we also need to know the impact of water content to the rocks. The water content will effect rock's shear strength, proof by the rocks condition which is brittle when it is dry and soft when it is wet. This research was done using sandstone that was taken from Geomechanics Laboratory of Mining Engineering Program, Faculty of Mining and Petroleum Engineering Bandung Institute of Technology. The results of laboratory scale of direct shear test were analyzed using Mohr-Coulomb and Patton criteria (1966). From the test results, it is known that the cohesion (c) of sandstone decreased from 510,30 kPa (at natural condition) down to 133,70 kPa (at wet condition). The internal friction angle (...) also decreased from 54,56o (at natural condition) down to 48,49o (at wet condition). The reduction of the shear strength is caused by fragments and clay minerals characteristics which are so reactive and very easy to absorb water so that the cohesion of the sandstone becomes weaker when it is wet. Besides that, pore water pressure at the voids of sandstone reduces the active normal stress (...) so that the shear stress (...) required to cause the shear failure becomes weaker. From the test results, it is also known that the shear surface roughness had a lot of influence on the shear strength because the normal stresses (...) applied on the direct shear tests were very low (under 20 % of UCS).